Изменение уровней цитокинов периферической крови человека in vitro под влиянием метаболитов бактерий, выделенных из многолетнемерзлых пород - Kolyvanova, S. S.; Kalenova, L. F.; Колыванова, С. С.; Калёнова, Л. Ф. (Tyumen State University Herald. Natural Resource Use and Ecology, 2018)
Microbiological research has shown viable microorganisms in the permafrost. The survival of bacteria in extremely cold conditions was the basis for the study of their byproduct (secondary metabolites). It is known that the bacterial cells’ number and their cultivation their cultivation temperature significantly affect their biological activity. For example, an experimental study of M3 strain of the Bacillus sp., isolated from permafrost, showed that the changes in cultivation temperature affected the enzymatic, immunotropic, and reparative properties of bacteria in vitro and in vivo. In this regard, the study of the effect of metabolites of microorganisms at the level of cytokine secretion, as indicators of immunological reactivity, seems relevant to create new immunotropic drugs in the future. The effect of secondary metabolites of the bacteria Bacillus sp. (strain M3) and Bacillus megaterium (strain 8/75-1), isolated from permafrost of different geological ages, on the synthesis inflammatory (TNF-α, IL-1β, IL-8, IL-2, IFN-γ ) and anti-inflammatory (IL-4, IL-10) cytokines by mononuclear cells of human peripheral blood by ELISA was analyzed in the article. Microorganisms Bacillus cereus (strain JP5832), isolated from the modern drug Bactisubtil, were used as control for comparison. Metabolites were obtained from a suspension of microorganisms taken in aliquots of 0.05 · 106 or 500 · 106 m. cl./ml, which incubated at temperatures of −5 °C and 37 °C. The revealed effects of the action of secondary metabolites were in a certain dependence on the temperature conditions of incubation of microorganisms, their number, and species. Metabolites of strain M3, used at a dose of 0.05 · 106 m. cl., induced the synthesis of cytokines of nonspecific immunity (IL-1β and IL-8), the development of cell-mediated (IFN-γ) and antibody-mediated (IL-4) immune reaction, and the action of metabolites strain 8/75-1 to a greater extent was aimed at increasing the secretion of IL-2, IFN-γ by mononuclear cells. The “warm” metabolites of strain 8/75-1 and the “cold” metabolites of strain M3, taken in a dose of 500 · 106 m. cl., have shown themselves to be active stimulants of secretion of practically the entire investigated spectrum of cytokine. В статье анализируется влияние вторичных метаболитов бактерий Bacillus sp. (штамм М3) и Bacillus megaterium (штамм 8/75-1) из многолетнемерзлых пород на синтез мононуклеарами про- (ФНО-α, ИЛ-1β, ИЛ-8, ИЛ-2, ИФН-γ) и противовоспалительных (ИЛ-4, ИЛ-10) цитокинов методом ИФА. Метаболиты получали из взвеси микроорганизмов, взятых в аликвотах по 0,05 · 106 или 500 · 106 м. кл./мл и инкубированных при температурах −5 °C и 37 °C. Выявленные эффекты действия метаболитов находились в определенной зависимости от температуры инкубации микроорганизмов, их количества и видовой принадлежности. Метаболитами от 0,05 ∙ 106 м. кл. Bacillus sp. штамма М3 было оказано стимулирующее влияние на синтез цитокинов, характеризующих реакции неспецифической (ИЛ-1β и ИЛ-8), клеточной (ИФН-γ) и гуморальной (ИЛ-4) иммунорезистентности, а действие метаболитов штамма 8/75-1 активировало деятельность клеточного иммунитета (ИЛ-2, ИФН-γ). Из метаболитов бактерий от 500 ∙ 106 м. кл. более активными стимуляторами секреции цитокинов оказались «тепловые» метаболиты штамма 8/75-1, а у штамма М3 — «холодовые».